(untitled) (Universal International Scientific Journal, 2026)
This article discusses the content, essence and role of inclusive education in the education system. The main principles of inclusive education, the importance of involving children with disabilities in the general education process, as well as the role of inclusive education in their adaptation to society and development are analyzed. The necessary pedagogical conditions for the effective organization of inclusive education and the tasks of teachers are also discussed.